High recurrence rate supports need for secondary prophylaxis in non-HIV patients with disseminated mycobacterium avium complex infection: a multi-center observational study. Issue 1 (December 2015) - Sridhar, Siddharth; Fung, Kitty; Chan, Jasper; Lam, Jimmy; Yip, Eric; Hung, Ivan; Wu, Alan; Que, Tak-Lun; Lau, Susanna; Woo, Patrick
Abstract Background Long-term outcomes in non-HIV immunocompromised patients with disseminatedMycobacterium avium complex (dMAC) infections are unknown and the need for post-treatment secondary prophylaxis against MAC is uncertain in this setting. The objective of this study was to determine the need of continuing secondary anti-MAC prophylaxis in non-HIV patients after completing treatment of the primary dMAC episode. Methods We conducted a ten-year multi-center analysis of non-HIV immunosuppressed patients with dMAC infections in Hong Kong. Results We observed sixteen patients with dMAC during the study period of which five (31 %) were non-HIV immunosuppressed patients. In the non-HIV immunosuppressed group, three patients completed a treatment course without secondary prophylaxis, one patient received azithromycin-based secondary prophylaxis and one patient was still receiving therapy for the first dMAC episode. All the three patients who completed treatment without being given secondary prophylaxis developed recurrent dMAC infection requiring retreatment. Conclusions In view of the high rate of dMAC infection recurrence in non-HIV immunocompromised patients following treatment completion, our data support long-term anti-MAC suppression therapy after treatment of the first dMAC infection episode in immunocompromised non-HIV patients, as is recommended for patients with advanced HIV. Tests of cell mediated immune function need to be evaluated to guide prophylaxis discontinuation in non-HIV patients.